PERAN TINGKAT PENDIDIKAN TERHADAP PENGETAHUAN PENYIMPANAN DAN PEMBUANGAN OBAT DI RUMAH PADA PASIEN RAWAT JALAN RSI SUNAN KUDUS - Pratiwi, Yulia; Khoiriyah; Annis Rahmawaty; Dian Arsanti Palupi; Rifda Naufa Lina; Jarot Yogi Hernawan (Jurnal Medicare, 2025)
Improper storage and disposal of medications at home can reduce drug quality, pose risks of poisoning, and contribute to environmental pollution. However, public knowledge remains low, as only 16.1% of respondents demonstrated good understanding of proper storage, and 52.6% lacked awareness of safe disposal methods. Education is considered a key factor in improving health literacy related to medication management. This study aimed to examine the relationship between educational level and knowledge of medication storage and disposal among outpatients at RSI Sunan Kudus. The research employed a descriptive quantitative approach, involving 392 respondents selected through purposive sampling. Data were analyzed using univariate analysis and Spearman Rank correlation. The majority of respondents were female (71.4%), aged 26–45 years (47.2%), had a senior high school/vocational education (53.8%), and were employed in the private sector (56.9%). Most respondents had moderate knowledge regarding storage (55.4%) and disposal (44.6%) of medications. A significant relationship was found between education level and knowledge of both storage (r = 0.532; p < 0.001) and disposal (r = 0.610; p < 0.001). More intensive education by pharmaceutical staff is recommended.